Applications and Mechanisms of Tripterygium Wilfordii Hook. F. and its Preparations in Kidney Diseases - Tong, Xue; Qiao, Yanheng; Yang, Yuanjian; Liu, Haizhao; Cao, Zhiyong; Yang, Bo; Wei, Lijuan; Yang, Hongtao (Frontiers in Pharmacology, 2022)
Tripterygium wilfordii Hook. f. (TwHF) is a Chinese herb containing a large number of monomers. The discovered and recognized anti-inflammatory and immune-regulating effects have made it attract more and more attentions in trials and clinical researches. The extraction and processing of TwHF for pharmaceuticals is a manifestation of the role of traditional Chinese medicine. However, TwHF is toxic. Optimization of TwHF preparations has become a requirement for the development of TwHF pharmaceuticals. Our article introduces the main preparations of TwHF on the Chinese market and their characteristics. In particular, we summarize the clinical applications and influential mechanisms of TwHF and its preparations in kidney diseases. Considering that nephropathy is closed related to immune inflammation and TwHF is a herb with a high number of monomers, the application of TwHF in kidney diseases may be much more complicated. By revealing the role and mechanisms of TwHF in kidney diseases, this study aims to provide more insights to basic and clinical studies about nephropathy.